2015
DOI: 10.1515/pac-2015-0407
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B2-sensitized degradation of the multifunctional drug Evernyl, in the presence of visible light – microbiological implications

Abstract: Taking into consideration the importance of the photooxidative effects in complex bioenvironments, this paper reports on the visible-light-promoted interactions between Evernyl (methyl 2, 4-dihydroxy-3,6-dimethylbenzoate, Ev) and vitamin B2 (riboflavin, Rf). Ev is a phenolic derivative, transparent to visible light, that possesses important antimicrobial activity. This compound is the first known natural, complete and specific human androgen receptor antagonist. Ev is profusely employed in personal-care produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…According to previous works, [14,28] this kind of system can be treated was found for FUR. Using the obtained 1  0 value of 5.73 ns, which is in concordance with the published fluorescence lifetime in methanol, [28,45] 1 k q = (2.7 ± 0.1) x 10 9 M -1 s -1 was calculated for FUR (Table 1).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous works, [14,28] this kind of system can be treated was found for FUR. Using the obtained 1  0 value of 5.73 ns, which is in concordance with the published fluorescence lifetime in methanol, [28,45] 1 k q = (2.7 ± 0.1) x 10 9 M -1 s -1 was calculated for FUR (Table 1).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…[11,12] Although FUR is transparent to visible light, it could be degraded by ultraviolet light, or by photosensitized processes induced by visible light irradiation of photosensitizers present in commercial formulations. Among these photosensitizers is Riboflavin (Rf), a visible-light absorbing vitamin with well-known photosensitizing properties, [13][14][15] abundant in meat, beer, wine, dairy products, and topical commercial products. [16][17][18] For example, different studies have reported the Rf-photosensitization of antioxidants, flavorings, or J o u r n a l P r e -p r o o f 5 food-related substances.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the rate of Predn photo-consumption induced by the presence of the enzyme, supports the idea of the involvement of the O 2 •species. It is well known [37,38]…”
Section: 2interaction Of Predn With Photogenerated Rosmentioning
confidence: 99%
“…It is well known that Rf generates the oxidative species: singlet oxygen (O 2 ( 1 Δ g )) and superoxide anion (O 2 •− ) upon visible light irradiation with quantum yields of 0.47 and 0.009 respectively, and the degradation of the contaminants may be due to the reaction between the pollutant and the excited electronic states of the Rf or with the reactive oxygen species (ROS) generated by these . The usual photochemical mechanism of Rf sensitization is rather complex, as shown by Scheme 1, in the presence of an eventual reactive molecule (Q) .…”
Section: Introductionmentioning
confidence: 99%
“…•À ) upon visible light irradiation with quantum yields of 0.47 and 0.009 respectively, and the degradation of the contaminants may be due to the reaction between the pollutant and the excited electronic states of the Rf or with the reactive oxygen species (ROS) generated by these (13,(16)(17)(18)(19). The usual photochemical mechanism of Rf sensitization is rather complex, as shown by Scheme 1, in the presence of an eventual reactive molecule (Q) (20,21). Upon absorption of a photon, Rf gives rise to its excited singlet state ( 1 Rf*, process [1]) and, through intersystem crossing, to the excited triplet state ( 3 Rf*, process [2]), 3 Rf* can transfer energy or an electron to ground state oxygen, O 2 ( 3 Σ g À ), in the solution, generating O ÁÀ 2 (process [3]) and O 2 ( 1 D g ) (process [11]).…”
Section: Introductionmentioning
confidence: 99%